The Value of Restitution and Diversion in the Law Enforcement of Criminal Sexual Violence Against Children - Widyaningrum, Tuti; Suharto, Andry (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2024)
The process of shifting the criminal justice system's case resolution process for offenses involving minor sexual assault to an outside location is known as diversion. One kind of diversion is returning money to victims of child sexual abuse; nevertheless, diversion and restitution are typically used less frequently in the criminal justice system. For this study, the following question was posed: Does law enforcement adhere to the juvenile criminal justice system when it comes to enforcing diversion and providing compensation for offenses involving sexual abuse of children? The study's technique is juridical-normative and follows the law. The study's findings show that law enforcement officers at all levels still stray from advised procedures even in the face of attempts to implement diversion within the criminal justice system. In order to make diversion mandatory during police investigations, public prosecutors' prosecutions, and judicial panel trials, rules and regulations that offer legal certainty are required.